Analysis on Mobile Internet Application Security Issues Based on the Cloud Computing Mode - Bingyi Fang; Yunyong Zhang; Jun Wu; Lei Xu (Dianxin kexue)
According to the safety objectives and the hierarchy of the c1oud computing mode1 of mobi1e internet, the security system was bui1t and the key security prob1ems were ana1yzed based on ana1ysis of the existing security techno1ogies in the network system.